Fundamentals of Constructing Frozen Type Earth Dams in the Arctic (Prinstipiabe osnov Vozvedeniia Plotin Merzlogo Tipa na Krainem Severe) - Biyanov,G F; Maslovskiy,G F; Toropov,L N (1977)
Available experience makes it possible to determine the main trends for improving the designs, methods and techniques of erecting frozen and thawed dams from soil materials and makes it possible to make some conclusions: 1) Frozen type dams may be erected on weak ice-saturated frozen soils if creation of dependable frozen antifiltration screens in the body of the dam is provided which are joined with the frozen soils of the base. 2) The design of the dam may be different depending on the organization of work to erect the dam and to create the frozen screen. If the freezing system is installed prior to the beginning of constructing the dam and the frozed screen is created simultaneously with erection of the dam, the tuckstone of the argillaceous core may be eliminated as a structural member. 3) When work in erecting dams is organized with simultaneous installation of the frozen screen, it is possible to use local frozen and thawed soil materials for embedding in the frozen core by making them one piece with water or clay mortars. The core of these dams may be erected by building up or pouring soil into the water. 4) The use of water-soluble heat carriers (brines) is not permitted to freeze the soils of the dam core since they thin the frozen soil in case of leaks. (Author) Trans. of Soviet-American Working Seminar 'Technology of Building Structures in Cold Climates', Moscow, May 77 16p.